Proceedings of the 21st Edition of the Great Lakes Symposium on Great Lakes Symposium on VLSI 2011
DOI: 10.1145/1973009.1973093
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of standby power reduction using voltage stacking in an 8Kb embedded FDSOI SRAM

Abstract: Voltage stacking has been proposed as an efficient solution for power delivery in high performance processors, for 3D ICs, for pin-limited ICs, and for implicit sleep mode (standby) DC/DC conversion. In this paper we demonstrate voltage stacking for an 8Kb embedded SRAM in 180nm fully-depleted SOI (FDSOI) which leads to 88.6% reduction in standby power, including overhead.The SRAM is formed of two 4Kb subarrayswhich are powered in parallel during active mode, and stacked in series during standby. The SRAM uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In [1] the authors used voltage stacking for 3D integrated circuits. In [3] the authors demonstrated the effectiveness of stacking scheme in saving standby power in SRAM by 88.6%. In [4] the authors have used voltage stacking to Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [1] the authors used voltage stacking for 3D integrated circuits. In [3] the authors demonstrated the effectiveness of stacking scheme in saving standby power in SRAM by 88.6%. In [4] the authors have used voltage stacking to Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page.…”
Section: Related Workmentioning
confidence: 99%
“…Similar solutions have been proposed earlier for 3D ICs, for pin limited ICs, for implicit high efficient DC-DC conversion, reduction of standby power in SRAM and power supply noise suppression [1][2][3][4].…”
Section: Introductionmentioning
confidence: 98%